An integrative model to understand consumers' trust and willingness to buy imported fresh fruit in urban China. Issue 6 (15th February 2021) - Feng, Ningning; Zhang, Airong; van Klinken, Rieks D.; Cui, Lijuan
Abstract : Purpose: The purpose of this paper is to develop an integrative model where perceived competence, perceived warmth and "clean green image" of an exporting country are drivers for Chinese consumers' trust in food quality and food safety, which in turn predict their willingness to buy fresh fruit from this country. Design/methodology/approach: Participants ( N = 1, 583) from the three metropolises in China were surveyed on their perceptions of the competence, warmth and clean green image of seven contrasting exporting countries and their trust in quality, trust in safety and willingness to buy fresh fruit imported from those countries. Findings: Results support the proposed integrative model, explaining 39%–55% of the variance in willingness to buy. Clean green image was the strongest predictor of willingness to buy through enhanced trust in food quality. The effects of country competence and warmth on willingness to buy through trust in food safety and quality varied with exporting country. Research limitations/implications: The integrative model and findings of this study can help agri-food industries develop an in-depth understanding of Chinese consumers and to develop targeted strategies to increase willingness to buy through improving consumer trust in food quality and safety. Originality/value: This study extends the country image framework which previously only consisted of human characteristics (i.e. perceived competence and warmth) by incorporating environmental characteristics (i.e. clean green image) in examining consumers' willingness to buy imported fresh fruit.